An evaluation model for software reuse processes - Al-Badareen, Anas Bassam; Selamat, Mohd Hasan; A. Jabar, Marzanah; Din, Jamilah; Turaev, Sherzod (Springer, 2011)
Software reuse is a major concern in many software development companies. It is one of the main strategies used to reduce the cost of software product development. Studies show that the reuse strategy is the most significant strategy in terms of effort and quality. That it could save the half of the software development effort and increase the quality of the software product. Different ways of software reuse are proposed and discussed. In this study, an evaluation model for software reuse is proposed. The model is developed in order to consider the new methods of software reuse. That developed based on the framework of develop a reusable software components through software development processes. The model is proposed in order to present the applicable methods of software reuse and to evaluate their cost.